The Triple Skilling Program: Implementation Design, Suitability of the Implementation, and Evaluate Program - Saputri, Agnes Nanda; Suminar, Tri; Raharjo, Tri Joko (Journal of Nonformal Education, 2023)
The unemployment rate is increasing due to the mismatch problem between skills and work needs. The Manpower Ministry develops Competency-Based Training into a triple skilling program as a solution to those problems. The study aims to analyze the implementation design, the suitability of the implementation of learning with established standards, and the achievement of implementing the triple skilling program. The research method used is qualitative phenomenology. The research subjects include program managers, training instructors, and training participants. The data collection techniques include in-depth interviews, observation, and documentation. The validity of the data used triangulation of sources and methods. The data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The study results explain that the technical implementation of program preparation was carried out by identifying and Training Needs Analysis (TNA) of the triple skilling program, selecting training participants, compiling curriculum, compiling materials, and determining training strategies. The implementation of the triple skill program was carried out from 1.5 months to 3 months. The method used is lecture and practice. The study results explain that the technical implementation of program preparation was carried out by identifying and Training Needs Analysis (TNA) of the triple skilling program, selecting training participants, compiling curriculum, compiling materials, and determining training strategies. The implementation of the triple skill program was carried out from 1.5 months to 3 months. The method used is lecture and practice. The instructor gave the training materials with 30% theory and 70% practice. The evaluation of the triple skill program includes the trainees' motivation in participating in the training, the number of trainees in the world of work, and the improvement of the economy of the trainees. In conclusion, the preparation of the triple skilling program has been adapted to the TNA in the world of work, the implementation of the curriculum is in accordance with the SKKNI standard, and it helps the community to be absorbed in employment and improve the community's economy.